2014
DOI: 10.1111/petr.12370
|View full text |Cite
|
Sign up to set email alerts
|

The World Transplant Games: An incentive to improve physical fitness and habitual activity in pediatric solid organ transplant recipients

Abstract: This prospective, interventional study examined the impact of training for the WTG on levels of health-related physical fitness and habitual activity in a cohort of pediatric SOT recipients. Physical fitness (FitnessGram(®) ) and habitual activity (HAES) measures were performed on participants (n = 19) in the WTG and compared to non-participant controls (n = 14) prior to and following the WTG. Pre-WTG exercise training was provided to participants. Participants demonstrated a statistically significant improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…Post-transplant rehabilitation: Exercise capacity and general fitness improves for children following lung transplant but remains reduced compared to age-predicted values[ 104 - 106 ]. Opportunities and access to rehabilitation post-transplant are often limited.…”
Section: Special Populationsmentioning
confidence: 99%
“…Post-transplant rehabilitation: Exercise capacity and general fitness improves for children following lung transplant but remains reduced compared to age-predicted values[ 104 - 106 ]. Opportunities and access to rehabilitation post-transplant are often limited.…”
Section: Special Populationsmentioning
confidence: 99%
“…The only study that measured balance found a decline in both balance and 6MWT distance over the intervention 26 . Improvements in flexibility were not seen in any study 17,18,20 …”
Section: Resultsmentioning
confidence: 92%
“…The most common Tx population was HSCT ( N = 9/12; 75%), followed by heart Tx ( N = 1/12; 8%), and two studies with a mixed population of solid organ Tx (SOT) recipients including heart or lung ( N = 1/12; 8%) and heart, lung, liver, or kidney ( N = 1/12; 8%) 17,18 . The most common study designs were non‐randomized controlled trials ( N = 5/12; 42%), 18–22 randomized controlled trials (RCT) ( N = 3/12; 25%) 23–25 and single‐arm pre‐post‐intervention studies ( N = 2/12; 33%) 26,27 . One study had double intervention arms comparing hospital versus home‐based exercise interventions, 17 and one study was described a case–control with an intervention component 28 .…”
Section: Resultsmentioning
confidence: 99%
“…8 Despite this increase in participation, there is limited empirical data regarding demographics, physical characteristics and medication regimes of TxA attending the Games. Existing data suggests participants at Transplant Games have predominantly been male kidney recipients with a mean age of 42-46 years [9][10][11][12][13] Data from the 1996 US Transplant Games 9 and 2012 Latin American Transplant Games 13 reported a high proportion (52%) of competitors managing one or more comorbid conditions while a small proportion (7%) experienced graft rejection within the 12 months prior to competition. Competitors at these events managed concurrent medications with continuous immunosuppressant management evident among nearly all TxA.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%